Estudo clínico do envenenamento experimental por Micrurus surinamensis em cobaias (Cavia porcellus) - Lilian de Paula Goncalves Reis (2017)
Micrurus surinamensis is a species of poisonous snake found in South America, in the Amazon region and popularly known as true coral or coral snake. This serpent differs from the others mainly due to it is semi-aquatic nature and fish-based feeding and there is a lack of studies on its venom especially in relation to its effects on mammals. Accidents involving corals are always severe because of the composition of its venom, which has three finger toxins (3FTx) and phospholipases (PLA2) in different proportions. There are no studies involving the neurological clinical condition, the cardiac effects, the blood alterations and the microscopic lesions that may be caused by the venom of M. surinamensis. Thus, the aim of this study was to evaluate guinea pigs (Cavia porcellus) experimentally poisoned with M. surinamensis venom, emphasizing the nervous and the cardiac (electrocardiographic) systems, in addition to evaluating blood tests and tissue exams (optical and electron microscopy). In order to perform the trial, twelve male animals were randomly divided into two groups (n = 6): control group and venom group. Each animal in the venom group received 0.75 g/g of M. surinamensis venom diluted in 0.2 ml PBS / BSA, inoculated intramuscularly (IM). The control group received 0.2 ml of PSA / BSA intramuscularly (IM). All animals underwent general physical examination, more specifically neurological exam, which was performed prior to venom or PBS/BSA inoculation (Time zero T0), 30 minutes after inoculation (Time 1 - T1), one hour after inoculation (Time 2 - T2) and approximately two hours after inoculation (Final Time - TF). Electrocardiogram and hematological tests were performed at T0 and TF. The animals which did not die two hours after the poisoning (TF), were euthanized and their corpses underwent necropsy and organ collection for microscopic analysis. The animals that received M. surinamensis venom presented neurological alterations with central, peripheral and autonomic nervous system involvement, marked by progressive respiratory difficulty, motor and mental state alterations, flaccid quadriplegia, total muscle paralysis and death. The electrocardiogram revealed severe arrhythmic alterations, such as 1st, 2nd and 3rd degree atrioventricular block, supra and ventricular extrasystoles. The leukogram showed an increase in total leukocytes count, specifically due to an increase in heterophils and monocytes, in addition to a decrease in lymphocytes. Serum biochemistry revealed a significant increase in creatine kinase enzyme and its MB fraction, aspartate aminotransferase and lactate dehydrogenase, indicating skeletal and cardiac muscle injury. Optical microscopy and transmission electron microscopy showed skeletal muscle necrosis in two animals of the venom group, however, rupture of skeletal and cardiac muscle fibers were observed only in electron microscopy. In conclusion, the M. surinamensis venom has neurotoxic and super-acute myotoxic activity (2h) in guinea pigs and is capable of causing severe neurological and cardiac electrical changes culminating in the death of the animals.